Konstruksi Kualitas Laporan Keuangan Bank Umum Syariah melalui Kompetensi, Independensi, dan Kualitas Audit Syariah: Studi Fenomenologi - Rusdi Salam (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to analyze how Shariah auditor competence, auditor independence, and Shariah audit quality are constructed in shaping the quality of financial reporting in Islamic Commercial Banks. A qualitative approach with a hermeneutic phenomenological method within an interpretive paradigm was employed. Participants were selected purposively and consisted of internal Shariah auditors, external auditors, Shariah Supervisory Board members, accounting managers and staff, compliance managers, and operational management. The findings reveal four major themes: Shariah auditor competence, auditor independence, Shariah audit quality, and the construction of financial reporting quality. Auditor competence is interpreted as the integration of technical expertise, Shariah knowledge, and professional experience, while auditor independence reflects objectivity grounded in integrity and trustworthiness (amanah). The interaction of these dimensions enhances Shariah audit quality by strengthening internal control, Shariah compliance, and financial reporting transparency. This study concludes that financial reporting quality is constructed through the integration of auditor competence, auditor independence, Shariah audit quality, and the internalization of Islamic values within Shariah governance.